2021
DOI: 10.3168/jds.2020-19603
|View full text |Cite
|
Sign up to set email alerts
|

Validation of milk mid-infrared spectroscopy for predicting the metabolic status of lactating dairy cows in Australia

Abstract: Increased concentrations of some serum biomarkers are known to be associated with impaired health of dairy cows. Therefore, being able to predict these biomarkers, especially in the early stage of lactation, would enable preventive management decision. Some health biomarkers may also be used as phenotypes for genetic improvement for improved animal health. In this study, we validated the accuracy and robustness of models for predicting serum concentrations of β-hydroxybutyrate (BHB), fatty acids, and urea nitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 45 publications
1
18
0
Order By: Relevance
“…Genetic correlations between ) and between fatty acids and MFA (0.28-0.56) were moderate and had large standard errors (0.13-0.32). The genetic correlations are in line with the prediction accuracies of the MIR equations reported by Ho et al (2020): prediction accuracies of the MIR equations were highest for urea and lowest for fatty acids. Despite having a genomic correlation significantly lower than 1, MBHB and MFA may still be useful for genomic prediction, especially if many more records would be available for MBHB and MFA than for BHB and fatty acids.…”
Section: Genetic Correlationssupporting
confidence: 83%
See 3 more Smart Citations
“…Genetic correlations between ) and between fatty acids and MFA (0.28-0.56) were moderate and had large standard errors (0.13-0.32). The genetic correlations are in line with the prediction accuracies of the MIR equations reported by Ho et al (2020): prediction accuracies of the MIR equations were highest for urea and lowest for fatty acids. Despite having a genomic correlation significantly lower than 1, MBHB and MFA may still be useful for genomic prediction, especially if many more records would be available for MBHB and MFA than for BHB and fatty acids.…”
Section: Genetic Correlationssupporting
confidence: 83%
“…The use of milk mid-infrared spectroscopy to improve genomic prediction accuracy of serum biomarkers I. van den Berg, 1 * P. N. Ho, 1 T. D. W. Luke, 1,2 M. Haile-Mariam, 1 S. Bolormaa, 1 and J. E. Pryce 1,2 using milk MIR to predict these serum biomarkers, with the value of R 2 obtained through random crossvalidation ranging between 0.21 and 0.92 (Belay et al, 2017;Grelet et al, 2019;Luke et al, 2019a,b;Pralle and White, 2020). In Australia, the equations for predicting serum BHB, fatty acids, and urea were initially developed by Luke et al (2019b) and have recently been validated by Ho et al (2020), with accuracies obtained through 10-fold random cross-validation of 0.60, 0.42, and 0.87, respectively. In this context, if MIR-predicted biomarkers are heritable, genetically correlated with the measured serum biomarkers concentrations, and available on a large number of individuals, they should theoretically help to increase the size of reference populations, and thereby aid the implementation of genomic prediction for health traits based on biomarkers.…”
Section: Many Authors Have Reported Promising Accuracies Whenmentioning
confidence: 99%
See 2 more Smart Citations
“…BUN requires a more difficult and costly blood sample, which limits the number of records. However, BUN can be accurately predicted using mid-infrared spectroscopy of a milk sample (Ho et al 2021). Our previous study showed that mid-infrared spectroscopy-predicted BUN (MBUN) and BUN are highly correlated, with a genetic correlation close to 1 (van den Berg et al 2021), and may therefore be considered as the same trait.…”
Section: Introductionmentioning
confidence: 99%